Posted by **Shaila** on Saturday, July 31, 2010 at 1:18pm.

let vector U = (vector u1, vector u2) vector V = (vector v1, vector v2) and vector W = (vector w1, vector w2) Prove each property using Cartesian vectors:

a) (vector U+V)+W = vector U+(v+W)

b) k(vector U+V) = k vector U + k vector V

c) (k+m)vector U = k vector U + m vector U

- cartesian vectors 2 -
**Damon**, Sunday, August 1, 2010 at 9:51am
U+V + W = (u1+v1, u2+v2)+(w1,w2)

= (u1+v1+w1 , u2+v2+w2)

=(u1,u2) + (v1+w1`, v2+w2)

= U + (V+W)

Do the others the same way.

## Answer This Question

## Related Questions

- calculus - State whether or not the following statements are true. Justify your ...
- Vectors - Verify using an example that Vector a + (Vector b • Vector c) is not ...
- Vectors - Verify using a specific example that (Vector a + Vector b) × (Vector a...
- Vectors - Verify using an example that Vector a + (Vector b • Vector c) is not ...
- Math - vectors - In the product F(vector)=q(V(vector)xB(vector), take q = 4, V(...
- Physics - Let vector A = 4i^ + 4j^, vector B = -2i^ - 5j^, and vector F = vector...
- Physics - Let vector A = 4i^ + 4j^, vector B = -2i^ - 5j^, and vector F = vector...
- Vectors - Explain why it is not possible for Vector a • (Vector b • Vector c) ...
- Mamthematics - Vectors - a) If vector u and vector v are non-collinear vectors ...
- Calculus - Dot Product - consider a rhombus ABCD a) find the resultant of vector...

More Related Questions